Dynamic modulation of corticospinal excitability and short-latency afferent inhibition during onset and maintenance phase of selective finger movement. Issue 6 (June 2016) - Cho, Hyun Joo; Panyakaew, Pattamon; Thirugnanasambandam, Nivethida; Wu, Tianxia; Hallett, Mark
Highlights: Motor surround inhibition was present only at the onset phase, but not at the maintenance phase of movement. Short-latency afferent inhibition (SAI) was decreased at onset, but not for the maintenance phase of selective movement in both active and surrounding muscles. SAI does not contribute either to initiation phase or to maintenance phase of selective movement. Abstract: Objective: During highly selective finger movement, corticospinal excitability is reduced in surrounding muscles at the onset of movement but this phenomenon has not been demonstrated during maintenance of movement. Sensorimotor integration may play an important role in selective movement. We sought to investigate how corticospinal excitability and short-latency afferent inhibition changes in active and surrounding muscles during onset and maintenance of selective finger movement. Methods: Using transcranial magnetic stimulation (TMS) and paired peripheral stimulation, input-output recruitment curve and short-latency afferent inhibition (SAI) were measured in the first dorsal interosseus and abductor digiti minimi muscles during selective index finger flexion. Results: Motor surround inhibition was present only at the onset phase, but not at the maintenance phase of movement. SAI was reduced at onset but not at the maintenance phase of movement in both active and surrounding muscles. Conclusions: Our study showed dynamic changes in corticospinal excitability and sensorimotor modulation for active and surrounding muscles in different movement states. SAI does not appear to contribute to motor surround inhibition at the movement onset phase. Also, there seems to be different inhibitory circuit(s) other than SAI for the movement maintenance phase in order to delineate the motor output selectively when corticospinal excitability is increased in both active and surrounding muscles. Significance: This study enhances our knowledge of dynamic changes in corticospinal excitability and sensorimotor interaction in different movement states to understand normal and disordered movements.